SENSORY-MOTOR ABILITY IN SOCCER SCORING FOR HIGH SCHOOL PLAYERS IN TIKRIT - Suha Jaber Miteb (Proximus Journal Publishing, 2026)
The research aimed to identify the level of cognitive ability and motor sense among high school team players in the accuracy of scoring in football, the researcher used the descriptive method in the survey method to suit it with the nature of the research, the research population identified the players of high school football teams, which are (320) players participating in the school football championship in the city of Tikrit for the academic year (2025/2026), and they are (20) school football teams, and the research sample was selected Deliberately, they are the (64) high school teams that qualified for the semi-finals, and after excluding a number of them, the sample number reached (52) players, and the researcher used two tests to measure the cognitive ability of the motor sense of scoring, the first is scoring from the penalty arc and the second is scoring from the penalty spot, and after finding the scientific foundations of the tests and doing the main experiment, the researcher processed the data obtained by the statistical package (SPSS)), the researcher reached a number of conclusions, namely that the players have a good and average level in the scoring test from the penalty arc from the penalty pole of stability, the player is blindfolded, and the test of scoring accuracy from the penalty point, and the levels have varied between acceptable and very good, which indicates the diversity in the level of sensory perception in scoring, while the selection of players for school teams comes as a result of self-selection and not relying on specific criteria, and the researcher recommended a number of points, the most important of which is that the Coaches of school teams should rely on criteria in selecting players, including the players' possession of the sensory cognitive ability, the necessity of using exercises that help develop sensory-motor cognitive abilities in training players, directing teachers in schools to invest in the physical education lesson, and developing curricula and teaching methods in a scientific and objective manner that helps raise the level of students in sensory-motor cognitive abilities
Keywords: Sensory-motor cognitiong; Scoring; Football